2010
DOI: 10.1001/archoto.2010.121
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomical Variability of the Maxillary Artery

Abstract: This study provides detailed information concerning the anatomical variability of the maxillary artery, which we hope will help prevent the arterial bleeding that may occur during mandibular or maxillary osteotomy or maxillectomy for ligation of the sphenopalatine artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 14 publications
(34 reference statements)
0
1
0
1
Order By: Relevance
“…Khan et al (2010) reported maxillary artery passed through the inferior alveolar nerve, splitting it into superficial and deep divisions in 3 of the 50 ITF fossas dissected. The first and second parts of the MA usually passed through the lateral aspect of lateral pterygoid muscle, with the inferior alveolar nerve, lingual nerve and buccal nerve on the medial side of the maxillary artery as reported by Kim et al (2010). There are also reports by Pretterklieber et al (1991) of unilateral variations of the IAN in the following forms: the MA, in addition to piercing the IAN, pierced LN and located deep to BN; the MA pierced only the IAN but passed deep to both the LN and BN; and the IAN formed a common trunk with the LN, which was pierced by the MA and ran deep to the BN.…”
Section: Discussionmentioning
confidence: 90%
“…Khan et al (2010) reported maxillary artery passed through the inferior alveolar nerve, splitting it into superficial and deep divisions in 3 of the 50 ITF fossas dissected. The first and second parts of the MA usually passed through the lateral aspect of lateral pterygoid muscle, with the inferior alveolar nerve, lingual nerve and buccal nerve on the medial side of the maxillary artery as reported by Kim et al (2010). There are also reports by Pretterklieber et al (1991) of unilateral variations of the IAN in the following forms: the MA, in addition to piercing the IAN, pierced LN and located deep to BN; the MA pierced only the IAN but passed deep to both the LN and BN; and the IAN formed a common trunk with the LN, which was pierced by the MA and ran deep to the BN.…”
Section: Discussionmentioning
confidence: 90%
“…In the anatomical study by Rosano et al 2 , the distance between alveolar crest and PSAA was measured as 11.25 mm. In Kim et al 12 's study, it was measured as 18.90 mm in the second premolar region and as 15.45 mm in the second molar region, and it was found that age and gender did not affect this distance. In our study, the distance of PSAA to the alveolar crest was found to be higher than the values in the literature and the mean value was found as 21.99 ± 4.59 mm.…”
Section: Discussionmentioning
confidence: 95%
“…In their study they conducted by using CBCT, Kim et al 12 reported the prevalence of PSAA as 64% in men and as 40% in women and they reported a signi cant correlation between gender and the prevalence of PSAA. On the contrary, no statistically signi cant correlation was found between the prevalence of PSAA and the gender of the participants (p = 0,603).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Эту артерию, в зависимости от отноше-ния к латеральной крыловидной мышце, условно принято разделять на 3 отдела: нижнечелюстной крыловидный, проходящий снаружи или кнутри (82 и 18% соответствен-но, по данным J. Kim и соавт. [24]) от латеральной крыло-видной мышцы, и крылонебный, располагающийся в крылонебной ямке и имеющий большую анатомическую вариабельность. Изучению клинической анатомии кры-лонебного сегмента ВЧА посвящен ряд анатомических исследований, что продиктовано развитием эндоскопиче-ской хирургии с разработкой методов дистального кон-троля ВЧА при удалении краниофациальных опухолей.…”
unclassified